Feminist Rehearsals : Gender at the Theatre in Early Twentieth-Century Argentina and Mexico - Farnsworth, May Summer (Book collections on Project MUSE., 2023)
"An exploration of gender at the theatre in early twentieth century Argentina and Mexico"--